Bluejacking as an advertisement tool / Nor Zuriati Zulkefly - Zulkefly, Nor Zuriati (2005)
This research was about the Bluetooth application called the Bluejacking. This application is known as the activity of sending anonymous messages to other Bluetoothenabled devices such as PDA's, Mobile Phones and Laptops within the range of the sender devices. This research focused on using this application via Laptop to bluejacked mobile phones and other Bluetooth-Enabled devices with the aid of a certain tool called Meeting Point. It would also focused on making this application as an advertisement tool, to send the promotional coupon to the devices that were located in the range. Here Bluejacking is used to 'hijack' the victims' devices to transmit the messages about the sales information. Other t h ^ that, this research would also concern about the Bluejacking security issue. Since it was known as a flaw to the Bluetooth technology, then this research would focused on proving that ridiculous perception. Although this research was more into study, but there would be some data testing to show the real situation of Bluejacking